基于实际设计齿廓斜齿轮的三维建模与有限元分析 - 王丽娜; 王铁; 张瑞亮 (Jixie chuandong)
The tooth root is an important unit in the finite element analysis of helical gear analysis. Usually the gear root transition curve is simplified. Taking into account the actual processing conditions in line with the actual design,through the creation of the filet curve,a deflection gear three-dimensional model is established by Pro/E parametric modeling function,and two gears model are analyzed and compared by Marc software.